Strategic approach to business intelligence and its impacts on organizational performance - Adıgüzel, Zafer (IGI Global, 2019)
Organizational structures have changed as a result of the widespread use of information technology, as well as the development of software programs and its daily use in all departments. When such technologies became more widespread throughout every sector, enterprises began to understand its effectiveness and have established information technology department requirements in their organizations. With time, these requirements have become integrated into whole organizations, thereby increasing the importance of business intelligence. Competitors, increasing uncertainties, and risks of the sector have resulted in the further development of the concept of business intelligence to support organizations and senior management wishing to achieve a competitive advantage and make strategic decisions. In other words, analyzing data and sharing it among the departments within the organization became significantly important as senior management use this information to make strategic decisions.
Keywords: Organizational; Business Intelligence; Strategic